Na companhia de um mais novo: funções do narrador-criança nas narrativas de infância bom dia, camaradas e meu pequeno país - Candido, Marina Ribeiro (2022)
This research aims at analyzing the childhood narratives of Good Morning Comrades (2014) by Angolan author Ondjaki and Small Country (2018) by Burundian author Gaël Faye. Our purpose is to suggest a more Afrocentric reading of both works, comparing the theoretical framework of autobiographies and autofictions to the teachings of African philosophies that reject the individualistic and self-centered idea of such concepts. We propose a reading starting from the concepts of escrevivência, by Conceição Evaristo (2020), and eu-refletorcoletivo, by Viviane Mendes de Moraes2 (2010). We also investigate the role of the child narrator in the mentioned works to demonstrate that this seems to be the most viable way to conduct the narratives surveyed here. We begin with the hypothesis that both authors choose to use the child narrator as a strategy to disguise narrative impossibilities, update the oral tradition, and break the silence imposed upon black people. The concept of childhood narrative comes from Helena Maria Assude Paio’s research (2010), and the concepts of autobiography and autofiction are analyzed based on the works of Lejeune (2014), Serge Doubrovsky (2014), and Philippe Gasparini (2014). These concepts will be related and discussed to support the research and reading of the books, based on the fundamentals of a qualitative descriptive study, and using analytical and hypothetico-deductive methods